Peningkatan Produktivitas Usaha Pengeringan Tepung Sagu Masyarakat melalui Introduksi Teknologi Tepat Guna di Kalimantan Barat - Sholahuddin Sholahuddin; Josua Parulian Hutajulu; Evi Gusmayanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Potentially, production of dried sago starch in Desa Arang Limbung, Sungai Raya, Kubu Raya District can be increased in term of quality and quantity. To achieve these, several problems have to be solved, i.e clean water availability for washing sago starch, washing mechanization to increase production capacity, and drying machine that efficient in operation and investment. Through IbM grant 2017, we have installed water filtration, sago washer, and solar dryer with greenhouse effect concept. Water filtration significantly increase the quality of water for use in washing sago starch and resulted in improved quality of sago starch. Mechanization of sago washing process and implementation of greenhouse effect dryer have increase capacity and efficiency of sago starch production. Generally, the introduced technology has been supported and accepted by stakeholder in Desa Arang Limbung. Further, the technology may support government policy in accelaration of food consumption diversity based on local resources.